Impairment of glutamate homeostasis in the nucleus accumbens core underpins cross-sensitization to cocaine following chronic restraint stress - Avalos, María P.; Guzman, Andrea S.; Garcia-Keller, Constanza; Mongi-Bragato, Bethania; Esparza, María A.; Rigoni, Daiana; Sanchez, Marianela A.; Calfa, Gastón D.; Bollati, Flavia A.; Cancela, Liliana M. (Frontiers in Physiology, 2022)
Though the facilitating influence of stress on drug abuse is well documented, the mechanisms underlying this interaction have yet to be fully elucidated. The present study explores the neurobiological mechanisms underpinning the sensitized response to the psychomotor-stimulating effects of cocaine following chronic restraint stress (CRS), emphasizing the differential contribution of both subcompartments of the nucleus accumbens (NA), the core (NAcore) and shell (NAshell), to this phenomenon. Adult male Wistar rats were restrained for 2 hours/day for seven days and, two weeks after the last stress exposure (day 21), all animals were randomly assigned to behavioral, biochemical or neurochemical tests. Our results demonstrated that the enduring CRS-induced increase in psychostimulant response to cocaine was paralleled by an increase of extracellular dopamine levels in the NAcore, but not the NAshell, greater than that observed in the non-stress group. Furthermore, we found that CRS induced an impairment of glutamate homeostasis in the NAcore, but not the NAshell. Its hallmarks were increased basal extracellular glutamate concentrations driven by a CRS-induced downregulation of GLT-1, blunted glutamate levels in response to cocaine and increased density of mushroom-shaped dendritic spines in pre-stressed animals. In addition, ceftriaxone, a known GLT-1 enhancer, prevented the CRS-induced GLT-1 downregulation, increased basal extracellular glutamate concentrations and changes in structural plasticity in the NAcore as well as behavioral cross-sensitization to cocaine, emphasizing the biological importance of GLT-1 in the comorbidity between chronic stress exposure and drug abuse. A future perspective concerning the paramount relevance of the stress-induced disruption of glutamate homeostasis as a vulnerability factor to the development of stress and substance use disorders during early life or adulthood of descendants is provided.